Enhancement of carbamazepine removal rate using Tetradesmus obliquus KNUA061 and NaOCl and utilization of the resulting biomass - Do, Jeong-Mi; Yeo, Hee-Tae; Do, Geum-Sook; Hong, Ji Won; Yoon, Ho-Sung (Frontiers in Energy Research, 2022)
Pharmaceutical and personal care products (PPCPs) are discharged into receiving water bodies mainly from sewage treatment plants. Due to the inefficient removal in conventional wastewater treatment facilities, PPCPs have become a major concern to aquatic ecosystems, water quality, and public health worldwide since they cause harmful effects on aquatic life and human even at low doses. Among the PPCPs, carbamazepine (CBZ) is one of the most commonly prescribed anticonvulsant drugs and consumed more than 1,000 tons per year. Due to its structural complexity, CBZ is known as recalcitrant compound highly stable during wastewater treatment. Consequently, it has become one of the most frequently detected pharmaceuticals in waste water, surface water, and even drinking water. In this study, Korean indigenous microalgae strains were tested as eco-friendly and cost-effective solutions for CBZ removal. Based on the preliminary biological CBZ degradation tests, Tetradesmus obliquus KNUA061 demonstrating the best CBZ removal rate was selected for further experiments. In order to increase strain KNUA061's CBZ removal efficiency, NaOCl, which is widely accepted in the water purification process, was used as an additional stimulus to induce stress conditions. At around 20 μg L−1 CBZ, addition of 1.0 mg NaOCl resulted in approximately 20% of removal rate increase without suppressing cells growth. Roughly 90% of CBZ remained its original form and the composition of the transformed secondary metabolites was less than 10% during the biodegradation process by the microalga. Based on the results of the antioxidant enzyme activities, degree of lipid oxidation, and amino acid contents, it was concluded that the redox-defence system in microalgal cells may have been activated by the NaOCl treatment. Biomass analysis results showed that higher heating value (HHV) of strain KNUA061 biomass was higher than those of lignocellulosic energy crops suggesting that it could be utilized as a possible renewable energy source. Even though its biodiesel properties were slightly below the international standards due to the high PUFA contents, the biodiesel produced from T. obliquus KNUA061 could be used as a blending resource for transportation fuels. It was also determined that the microalgal biomass has acceptable feasibility as a sustainable dietary supplement feedstock due to its high essential amino acid contents.